Aerobic Conditions Enhance the Photocatalytic Stability of CdS/CdOx Quantum Dots. Issue 69 (27th June 2018) - Wakerley, David W.; Ly, Khoa H.; Kornienko, Nikolay; Orchard, Katherine L.; Kuehnel, Moritz F.; Reisner, Erwin
Abstract: Photocatalytic H2 production through water splitting represents an attractive route to generate a renewable fuel. These systems are typically limited to anaerobic conditions due to the inhibiting effects of O2 . Here, we report that sacrificial H2 evolution with CdS quantum dots does not necessarily suffer from O2 inhibition and can even be stabilised under aerobic conditions. The introduction of O2 prevents a key inactivation pathway of CdS (over‐accumulation of metallic Cd and particle agglomeration) and thereby affords particles with higher stability. These findings represent a possibility to exploit the O2 reduction reaction to inhibit deactivation, rather than catalysis, offering a strategy to stabilise photocatalysts that suffer from similar degradation reactions. Abstract : Photocatalytic H2 evolution undertaken by CdS quantum dots is greatly enhanced in highly alkaline conditions under air when compared to inert conditions. Air prevents the over‐accumulation of metallic Cd 0 sites on the particle surface and therefore increased stability of the quantum dots.